Empowering MSME Entrepreneurs Through Digital Marketing Mentoring and Digital Financial Literacy in Tinambung Subdistrict, Indonesia - Fitriani Latief; Ahmad Firman; Hardianty Askar; Indrawan Azis; Andi Ircham Hidayat; Shandra Bahasoan; Dara Ayu Nianty; Asniwati Asniwati; Dirwan Dirwan; Eka Aussie Hadiningtyas; Mutiasari Mubyl Handaling; Anita Anita (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This program was initiated in response to low adoption of digital marketing and financial literacy among MSMEs in Tinambung Subdistrict, resulting in limited market reach and poor business management. The initiative aims to enhance MSMEs’ capabilities in digital marketing and financial literacy and to promote business self-reliance. Research Method: The activity was conducted in February 2026 in the Tinambung Subdistrict, Polewali Mandar Regency, and involved 30 MSME operators across the retail, food service, and service sectors. The method used was a participatory approach through outreach, technical training, and hands-on coaching, with observations, interviews, and questionnaires serving as evaluation tools. Results and Discussion: Before the intervention, only 23% of partners had a digital business account, and 26% kept financial records. The activities were implemented in phases, ranging from outreach to monitoring. The results showed significant improvements: digital account ownership rose to 83%, understanding of promotional content to 78%, financial record-keeping to 80%, and financial segregation to 76%. Implications: This program promotes digital adoption and financial management among SMEs. Ongoing support is recommended to ensure the sustainability of SMEs’ digital transformation.